Exploration of Parents' Digital Parenting Efficacy through Several Demographic Variables - Yaman, Fatih; Donmez, Onur; Akbulut, Yavuz; Yurdakul, Isil Kabakci; Coklar, Ahmet Naci; Guyer, Tolga (TURKISH EDUCATION ASSOC, 2019)
As digital technologies develop, they provide individuals with new opportunities in various areas of daily life. However, these technologies also bring about some potential risks. Through digital technologies, several risks including but not limited to malicious content, cyberbullying, pornography, and sexually-explicit messages can easily reach out to households. The most vulnerable group for such risks is the children. As parents are primarily responsible for the well-being of their children, they have an important role in protecting the children in the digital environment. Parents need to get acquainted with the digital age so that they could protect their children from the risks pertaining to the use of digital technologies. The purpose of this study was twofold: (a) to identify digital parenting efficacy domains and their indicators, and (b) to examine parents' efficacy levels in terms of some demographic variables through a measure based on the identified indicators. The study was survey research with two phases. In the first phase, based on a literature review and a focus group interview with experts, digital parenting efficacy fields and their indicators were identified. In the second phase, a digital parenting self-efficacy scale was developed and administered to 576 parents in Eskisehir region to explore the participants' self-efficacy levels based on parenting roles, internet use, income level, occupation, and educational level. The digital parenting competencies and their indicators used in the scale development process consisted of seven dimensions. Through the participation of separate samples of parents, the factorial structure of the scale was examined through exploratory (n=520) and confirmatory factor analyses (n=556). After construct validity steps, indicators were gathered under three factors as digital literacy, digital safety, and digital communication. These indicators did not differ based on parents' role in the process, internet use, socio-economic status, occupation, and level of education.
Keywords: Digital parenting; Online parenting; Internet parenting; Internet safety; Digital safety